POLA ASUH ORANGTUA DALAM MENGEMBANGKAN KETERAMPILAN SOSIAL ANAK (STUDI KASUS KELUARGA SARIFUDIN, JL. SUKA KARYA PERUMAHAN KARYA PESONA MANDIRI BLOK S 21 RT 01 RW 27 PANAM PEKANBARU) - Wahyu Sari Suryani; Mahmud Alpusari; Eddy Noviana (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2019)
The purpose of this study was to describe in-depth how parenting Sarifudin family in developing the social skills of children. In this research, the type of research used by the author is descriptive qualitative research with approach case studies. The subject of this research is the third child of father Sarifudin named Neriza Safitri. Source data are taken from parents Neriza consisting of a father and mother, a third son named Neriza Safitri and neighbors near Sarifudin family. Using data collection techniques of observation, interview, documentation, and triangulation. The data analysis technique used is the reduction of data, data presentation, and conclusion. From the results of research that has been done can be concluded that in the family Sarifudin parenting that is applied to his son was a democratic type of parenting. Democratic parenting is parenting that gives to the son demands at once responsive to the will and the will of the child. Democratic parents will be assertive, let children choose what he thought good, encouraging children to take responsibility for the choices, but still set the standards and a clear limitation on the child and always watching him. They are still engaged in intensive communication and warm as well as responsive to the needs of the child. Warm communication allows the existence of discussions. In applying the discipline of democratic parents will be sportsmanship, meaning that when children do not comply with the rules of the parents and are able to explain the reason, parents are willing to hear and understand.